Pelayanan tenaga administrasi sekolah urusan keuangan berbasis teknologi informasi di SMK se-kota Bukittinggi - Dara Salsabila Triputri; Rusdinal Rusdinal; Irsyad Irsyad; Sulastri Sulastri (Universitas Negeri Padang, 2021)
In this study regarding the service of information technology-based financial affairs administration staff in SMK in Bukittinggi to find out and study how well the services provided by the financial affairs administration staff. Have provided good service to service recipients. This can be seen from the aspects of 1) simplicity, 2) clarity, 3) time certainly, 4) accuracy, 5) security, 6) responsibility, 7) completeness of facilities and infrastructure, 8) comfort. This study uses a population research method, namely all populations are subjects to be studied. Therefore, the population of this study is all administrative staff of financial affairs at vocational high schools in Bukittinggi, amounting to 25 people from 9 schools. The instrument used in this study was a questionnaire with a likert scale. From the results of the study, it has been found that the service of information technology-based financial affairs school administrative staff at SMK in Bukittinggi City get a score of 4,17 with a good category.